PENGARUH MODEL PEMBELAJARAN INTERAKTIF SETTING KOOPERATIF TERHADAP HASIL BELAJAR BIOLOGI KELAS X SMAN 2 BONE - Hasnaeni Hasnaeni; Muh. Rapi; Syahriani Syahriani (Al-AHYA: Jurnal Pendidikan Biologi, 2021)
This study is intended to know the effect of the cooperative setting interactive learning model (PISK) on the Biology learning outcomes of students. This quasi-experimental research has a non-equivalent posttest-only control group design. The population is class X MIPA SMA Negeri 2 Bone as many as 210 students. The sampling technique used is a purposive sampling technique. The sample is 50 people consisting of two classes, namely class X MIPA 2 as an experiment using the PISK model as many as 25 students and class X MIPA 1 as a control class totaling 25 students. The research instruments were in the form of learning outcomes tests and observation sheets. Data analysis techniques are descriptive analysis and inferential analysis using prerequisite tests and independent sample t-test. The data obtained from learning outcomes in the experimental class were in the high category with an average value of 79. Meanwhile, the control class obtained an average value of 75.20 with a high category. Hypothesis testing showed differences in learning outcomes taught with the PISK model and with the lecture method. The effectiveness test shows that learning using the PISK model is more effective than direct learning.